(untitled) (Research, Society and Development, 2021)
The objective was to identify the possible diagnoses and nursing interventions in patients affected by the mild form of COVID-19 using the CIPE 2019 taxonomy. This is an integrative literature review, carried out by means of a bibliographic survey based on secondary data. The present study analyzes and synthesizes a compilation of scientific evidence related to the guiding question and allows for obtaining full conclusions about the research problem. Nine articles were selected. When reading the selected studies, an analysis of the most frequent signs and symptoms was obtained among adult patients with COVID-19. The prevalence of clinical conditions with systemic involvement was observed, including fever, fatigue, myalgia, and respiratory impairment, such as non-productive cough, dyspnoea, hemoptysis. In addition to these, manifestations related to the nervous system were observed, such as headache, anosmia, ageusia, as well as those present in the gastrointestinal system, in view of diarrhea, nausea and vomiting. From the most prevalent manifestations, Nursing Diagnoses and Interventions were listed. The present study has relevance for elucidating the Nursing Diagnoses and the nurses’ conduct in the face of mild cases of COVID-19, in order to establish the systematization of care in a satisfactory manner, in the face of events related to this condition.